ASSESSING THE IMPACT OF ONLINE LANGUAGE LEARNING PLATFORMS ON ESL LEARNERS’ LANGUAGE PROFICIENCY (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
The advent of online language learning platforms has revolutionized languageacquisition, particularly for English as a Second Language (ESL) learners. With theincreasing prevalence of digital tools in education, these platforms offer flexible,interactive, and accessible means of learning.